PS02.192: TWO CASES OF PRIMARY MALIGNANT MELANOMA OF ESOPHAGUS TREATED WITH SUBTOTAL ESOPHAGECTOMY. (14th September 2018) - Hirohata, Ryosuke; Emi, Manabu; Hamai, Yoichi; Ibuki, Yuta; Okada, Morihito
Abstract: Background: Malignant melanoma of the primary esophagus is rare, in general it has high malignancy and poor prognosis. We report two cases of early-stage primary malignant melanoma of esophagus (PMME) underwent subtotal esophagectomy. Methods: Case presentation Results: [Case 1]A 66-year-old man was pointed out a black legion on the lower esophagus by upper gastrointestinal endoscope for screening purposes. The lesion was diagnosed as malignant melanoma by biopsy. In addition, another black lesion was also found in the pharynx, but there was no malignant cell. Other examinations did not reveal any findings of lymph node metastasis and distant metastasis. We diagnosed PMME (T1aN0M0 Stage 0) and performed surgical resection. Pathologically it was pT1a (LPM), pN0. There is no recurrence, and it is under observation. [Case 2] A 51-year-old woman was conducted upper gastrointestinal endoscopy for the purpose of scarring epigastric pain, and a black lesion was pointed out in lower esophagus. Surgical resection was performed with diagnosis of PMME (T1bN0M0 Stage I). The pathological stage was pT1a (MM), pN0. Conclusion: The 5 year survival rate of malignant melanoma of primary esophagus is poor with about 30 to 35%, and especially in cases with lymph node metastasis, the survival rate further decreases. The both cases were discovered accidentally by endoscopic examination, leading to early diagnosis and early treatment. Therefore, long survival is expected. There is also a report that melanosis is associated with melanoma, so case 1 requires careful follow-up observation. Disclosure: All authors have declared no conflicts of interest.